CIVIL ENGENEERING OF EDUCATION STUDENTS PERCEPTIONS OF LEARNING INFRASTRUCTURE MAINTENANCE - Malik, Abdul (2013)
The efforts to sustain the learning infrastructure, with maintaining learning infrastructure as described in the Indonesian Government Regulation No. 19 Year 2005 on National Education Standards Article 47 point 1. That the maintenance of educational facilities as referred to in Article 42 up to 46 becoming the responsibility of the educational unit concerned. Educational unit that includes students, who also have a responsibility to infrastructure maintain. While in the fact the students still think that responsibility to maintain infrastructure. Student perceptions affect the students' responsibility to maintain learning infrastructure, which is closely related to the sustainability of the quality of the learning infrastructure.This study aims to: 1) To know the descriptive of students in Civil EngeneeringDepartemen of Education perceptions about learning infrastructure maintenance. 2) To know the descriptive of male and female students in Civil EngeneeringDepartemen of Education perceptions about learning infrastructure maintenance. 3) To know the descriptive of students in Civil EngeneeringDepartemen of Education perceptions in each class of 2010, 2011, and 2012 in learning infrastructure maintenance. 4) To know the descriptive of each Study Programs there are PTB, TS-S1 and TS-D3 in Civil EngeneeringDepartemen of Education perceptions of learning infrastructure maintenance. This research is a descriptive study which use qualitative research methods and parametric analysis techniques the sample of this research were 84 students from 332 studentsof Civil Engeneering of Education Program. From the analysis of the data, theresult shows that most of the student in Civil EngeneeringDepartemen of Education has a positive perceptionsabout learning infrastructure maintenance but there are still a few student who has not. It can be conclude that not all Civil Engeneering of Education student have a positive perceptions about learning infrastructure maintenance. Keywords: Perceptions, Maintenance, LearningInfrastructure.